2016
DOI: 10.7554/elife.13732
|View full text |Cite
|
Sign up to set email alerts
|

The role of piriform associative connections in odor categorization

Abstract: Distributed neural activity patterns are widely proposed to underlie object identification and categorization in the brain. In the olfactory domain, pattern-based representations of odor objects are encoded in piriform cortex. This region receives both afferent and associative inputs, though their relative contributions to odor perception are poorly understood. Here, we combined a placebo-controlled pharmacological fMRI paradigm with multivariate pattern analyses to test the role of associative connections in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 77 publications
(97 reference statements)
1
23
0
Order By: Relevance
“…In our study, we found a clear differentiation between the functional connectivity patterns of human frontal and temporal piriform subdivisions, suggesting these two areas play different roles in olfactory processing in the human brain (Albrecht et al, 2010; Bao et al, 2016; Bensafi et al, 2007; Howard et al, 2009; Plailly et al, 2012; Porter et al, 2005; Zelano et al, 2005). This distinction between frontal and temporal piriform cortices was robust, surviving across k values and hemispheres.…”
Section: Discussionmentioning
confidence: 56%
“…In our study, we found a clear differentiation between the functional connectivity patterns of human frontal and temporal piriform subdivisions, suggesting these two areas play different roles in olfactory processing in the human brain (Albrecht et al, 2010; Bao et al, 2016; Bensafi et al, 2007; Howard et al, 2009; Plailly et al, 2012; Porter et al, 2005; Zelano et al, 2005). This distinction between frontal and temporal piriform cortices was robust, surviving across k values and hemispheres.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, we also noted that over half of the ipsilateral OLF inputs to the PPC came from the ipsilateral APC. A previous study demonstrated that by using the GABA(B) receptor agonist to attenuate PC associational inputs, pattern separation of within-category odors is interfered within the PPC (Bao et al, 2016), meaning that the neural activities in the PC, especially the PPC, may strongly be affected by their associational connections. It could be speculated that the PPC may be in higher associative functions.…”
Section: Input Patterns To Distinct Subareas Of the Pcmentioning
confidence: 99%
“…The APC and PPC play different roles in olfactory processing including odor response and learning (Litaudon et al, 2003;Gottfried et al, 2006;Kadohisa and Wilson, 2006;Calu et al, 2007). For instance, the APC encodes odor identity and anticipation, and can be activated not only by odor stimuli but also by odor associated values or contextual cues (Zinyuk et al, 2001;Gottfried et al, 2006;Kadohisa and Wilson, 2006;Roesch et al, 2007); whereas the PPC seems to encode more associated information for it to be activated in tasks that require encoding of odor similarity or odor quality (Kadohisa and Wilson, 2006;Calu et al, 2007;Howard et al, 2009;Zelano et al, 2011;Bao et al, 2016;Grau-Perales et al, 2019). In addition, accumulating evidence from research has also revealed distinct susceptibilities of different PC subareas to seizure generation (Loscher and Ebert, 1996;Ekstrand et al, 2001;Yang et al, 2006;Vismer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the current form of the inhibitory learning rule forestalls manifold learning; its more sophisticated replacement may require expansion of the network to include the feedback loop between MOB and PCx, which in the biological system supersedes intrinsic MOB gamma with slightly slower (beta band) coherent oscillations between these two structures (Cenier et al, 2009 ; Frederick et al, 2016 ). Indeed, existing efforts to study the neuroscience of odor categorization have focused on the PCx and its associated limbic regions (Bao et al, 2016 ; Qu et al, 2016 ), and analogous studies in insects also suggest that categorical processing incorporates plasticity in peripheral networks together with higher-order olfactory structures (Locatelli et al, 2016 ; Strube-Bloss and Rossler, 2018 ). Finally, the rules by which adult-generated interneurons are incorporated into the neuromorphic network also are simplified, privileging strict categorization over similarity-dependent generalization processes.…”
Section: Theoretical Capacities Of Olfactory Bulb Circuitsmentioning
confidence: 99%